Proses Penyembuhan Luka Diabetik Yang Menggunakan Terapi Ozon Pada Pasien Dengan Diabetes Mellitus - Hidayah, Nurul; Yuna Annisa Salsabila; Nurwidji; Wanda Putri Ihsani (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Diabetic wounds are the most common complication of diabetes mellitus. Ozone therapy is a complementary therapy that can accelerate and improve the healing process of diabetic wounds. The advantages of ozone therapy are its antimicrobial effects through increased tissue oxygenation, stimulation of angiogenesis, and modulation of the inflammatory response. The purpose of this study was to determine how diabetic wounds are treated after ozone therapy. The design used was a descriptive case study using two clients with diabetes mellitus and diabetic wound complications who visited the Mojopahit Wocare Clinic in Mojokerto Regency as research subjects. The results of this study were obtained in subject I, wounds closed faster and regenerated well with a reduction in the area of ??the wound in the subject of approximately 2.13 cm2/day with an estimated wound healing time of 10 weeks, and in subject II, wounds closed faster and regenerated well with a reduction in the area of ??the wound in the subject of approximately 4.67 cm2/day with an estimated wound healing time of 7 weeks. Therefore, ozone therapy is very helpful in the healing process of diabetic wounds and for a nurse to have a role as an educator in providing information, providing services and helping clients in increasing the level of health knowledge, especially about ozone therapy for healing diabetic wounds.